VALIDITY IN RESEARCH: ENSURING CREDIBLE AND RELIABLE RESULTS - Turdiyeva Fotima; Kenjayeva Marg'iyona; Qurbonova Dildora (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Validity is a crucial concept in research, referring to the extent to which a test, measurement, or study accurately represents what it claims to measure. It determines the credibility and applicability of research findings. Validity is essential to maintain scientific integrity and ensure the reliability of conclusions drawn from a study. This article explores different types of validity, their importance, and how to enhance validity in research.